Bentuk Frasa Preposisional dalam Caption Instagram Alumni Indonesian Idol Season X Kajian Sintaksis - Dina Sri Puspitasari; Dinda Wulansari; Khusnul Nur Mawar Sari; Mita Miftaqul Muhclisah; Nuvitaliya Rahmawati; Taswirul Afkar (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
This study aims to analyze the forms of prepositional phrases used to convey meanings and messages in the Instagram captions of Indonesian Idol Season X alumni. The research employs a descriptive qualitative approach using the listening and note-taking techniques to collect and classify linguistic data. The data sources consist of Instagram captions posted by Ziva Magnolya, Tiara Andini, Mahalini Raharja, Lyodra Ginting, and Keisya Levronka, who actively use social media as a platform for communication and self-expression. The analysis focuses on identifying the structural forms and functions of prepositional phrases within the captions and examining how these linguistic elements contribute to the delivery of information, emotions, and persuasive messages. The findings indicate that the use of prepositional phrases varies among the singers in terms of structure, frequency, and communicative function. These variations reflect each singer’s distinctive writing style and communication strategy in interacting with followers while strengthening the clarity, coherence, and contextual meaning of the captions. The study also demonstrates that prepositional phrases play an important role in enriching sentence construction and supporting effective communication in digital discourse. Therefore, the findings contribute to the development of syntactic studies, particularly those related to language use on social media, and provide useful references for future research on linguistic structures in digital communication.